The Relationship between Locus of Control and Decision-Making among Undergraduate Students - Dayang Nur Balqis, Mohd Hairul Nizam; Norehan, Zulkiply (Secholian Publication, 2024)
The present study investigates the relationship between the locus of control and decision-making among undergraduate students. The research sample comprises 200 Cognitive Science students from the Universiti Malaysia Sarawak; it consists of an equal number of male and female students and first-year and final-year students. Two instruments were used to assess the participants: the Levenson Locus of Control Scale and the “How Good Is Your Decision-Making?” Scale. The findings reveal higher scores for male students in decision-making and internal locus of control, while females demonstrated higher external locus of control scores. A positive correlation was also observed between the internal locus of control and the effectiveness of decision-making processes. However, no significant difference was found in locus of control and decision-making abilities between first-year and final-year students. This indicates that these traits remain relatively stable across academic progression. The present study highlights the importance of nurturing an internal locus of control, especially in an academic setting, to enhance students’ decision-making abilities and overall psychological well-being. These findings offer insights into strategies that could be practical for reinforcing students’ internal locus of control while also enhancing their decision-making abilities.